2017
DOI: 10.1148/radiol.2017161435
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Xanthomas: Fat-Water Separation at Baseline and after Treatment

Abstract: Purpose To investigate the fat-water content of Achilles tendon xanthomas at baseline and after treatment and to compare this assessment with that of ultrasonography (US) and other magnetic resonance (MR) imaging-based parameters. Materials and Methods Forty-eight Achilles tendons with clinically apparent xanthomas in 24 patients with familial hypercholesterolemia (FH) (six men, 18 women; mean age ± standard deviation, 58 years ± 9) were compared with 20 Achilles tendons in 10 control subjects without FH (two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Neoangiogenesis accompanies chronic inflammation and may play an important role in the deposition of cholesterol crystals within the Achilles tendon, which leads to glycosaminoglycan accumulation, chronic tendon degeneration, and xanthoma formation. Griffith et al showed an elevation in signal intensity in ATX on the Dixon-water images that indicated an increase in the water content of the Achilles tendon (6), which was in line with the findings in our two cases. The increase in water content of ATX might be attributed in part to neoangiogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Neoangiogenesis accompanies chronic inflammation and may play an important role in the deposition of cholesterol crystals within the Achilles tendon, which leads to glycosaminoglycan accumulation, chronic tendon degeneration, and xanthoma formation. Griffith et al showed an elevation in signal intensity in ATX on the Dixon-water images that indicated an increase in the water content of the Achilles tendon (6), which was in line with the findings in our two cases. The increase in water content of ATX might be attributed in part to neoangiogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…The phenomena of increased hysteresis, or reduced return of stored energy, in participants with FH could be explained in several ways. First, AT TXT has been shown to have increased water content, which is associated with increased viscosity and therefore increases fluid efflux, removing more energy from the tendon in the form of heat [ 29 , 45 ]. Second, poorly aligned collagen, cholesterol deposits, swelling, inflammation, and angiogenesis could affect the tendon’s extension mechanisms, by increasing friction internally and externally, also increasing heat dissipation into surrounding tissues [ 8 , 16 , 22 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, Young’s modulus would be used as an appropriate measure for comparing tendon properties by removing the influence of tendon dimensions. However, we chose not to use measures that incorporate CSA measures, as TXT may not hold any load bearing qualities and would therefore skew the results and comparison between the two groups [ 29 ]. All variables were calculated for the ground contact portion of the gait cycle only.…”
Section: Methodsmentioning
confidence: 99%
“…Utilization of the fat only image allows for water suppression such that fat infiltration can be quantified without distortion from water signal [ 12 ]. The Dixon method has proven to be effective in abdominal fat quantification [ 13 ], and recent research has supported its utility for fat quantification in the lower extremity, particularly to quantify lipid infiltration of calf musculature in patients presenting with Achillodynia [ 14 ]. Griffith et al [ 15 ] have recently established, using magnetic resonance spectroscopy, that the Dixon method is able to detect cholesterol in the Achilles tendons, and that the tendons from people with FH display the predicted increase in fat signal compared to healthy tendons.…”
Section: Introductionmentioning
confidence: 99%